2010
DOI: 10.5204/jld.v3i2.50
|View full text |Cite
|
Sign up to set email alerts
|

Matching intention with agency: Lessons from practice

Abstract: Keywords social networks, communities of practice, agency of technologyA major difficulty for many doctoral students is their transition from professional practitioner to researcher and scholar. The struggle that many experience in this transition is in the development of a theoretical or conceptual standpoint for argumentation (Fox, Greene & Weese, 1999;Leshem, 2007). It was thought that the use of a collaborative wiki environment in a Professional Doctorate program in a Queensland university might ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Empirical research studies have shown that students might feel too intimidated to participate because of the public nature on wikis. For instance, some students felt uncomfortable displaying their works in progress in front of their peers on a class wiki (Beames, Klenowski, & Lloyd, ; de Pedro et al, ; Lin & Kelsey, ). Before addressing students' concerns, there is a need to help students understand ‘why wikis?’ and ‘how openness on wikis benefits learning’.…”
Section: Design Theorymentioning
confidence: 99%
“…Empirical research studies have shown that students might feel too intimidated to participate because of the public nature on wikis. For instance, some students felt uncomfortable displaying their works in progress in front of their peers on a class wiki (Beames, Klenowski, & Lloyd, ; de Pedro et al, ; Lin & Kelsey, ). Before addressing students' concerns, there is a need to help students understand ‘why wikis?’ and ‘how openness on wikis benefits learning’.…”
Section: Design Theorymentioning
confidence: 99%
“…Only a few recent studies specifically look into how postgraduate research students conceive and approach the use of ICT in their research (Beames, Klenowski, & Lloyd, 2010;Carpenter, 2012;Stelma, 2010). One of the largest of these, tracking three years' research behaviour of Generation Y doctoral students, found that research students were highly competent ICT users and sophisticated information seekers; however, they were quite risk averse and conservative about embracing new technologies in their research (Carpenter, 2012).…”
Section: Students' Attitudes and Approaches Towards The Role Of Ict Imentioning
confidence: 99%